Climate-driven terrestrial inputs in ultraoligotrophic mountain streams of Andean Patagonia revealed through chromophoric and fluorescent dissolved organic matter - García, Roberto Daniel (2015)
Fluvial networks transport a substantial fraction of the terrestrial production, contributing to the global carbon cycle and being shaped by hydrologic, natural and anthropogenic factors. In this investigation, four Andean Patagonian oligotrophic streams connecting a forested catchment (~ 125 km2) and draining to a double-basin large and deep lake (Lake Moreno complex, Northwestern Patagonia), were surveyed to analyze the dynamics of the allochthonous subsidy. The results of a 30 month survey showed that the catchment supplies nutrients and dissolved organic matter (DOM) to the streams. The eruption of the Puyehue–Cordón Caulle at the beginning of the study overlapped with seasonal precipitation events. The largest terrestrial input was timed with precipitation which increased particulate materials, nutrients and DOM through enhanced runoff. Baseline suspended solids and nutrients were very low in all the streams (suspended solids: ~ 1 mg/L; total nitrogen: ~ 0.02 mg/L; total phosphorus: ~ 5 μg/L), increasing several fold with runoff. Baseline dissolved organic carbon concentrations (DOC) ranged between 0.15 and 1 mg/L peaking up to three-fold. Chromophoric and fluorescent analyses characterized the DOM as of large molecular weight and high aromaticity. Parallel factor modeling (PARAFAC) of DOM fluorescence matrices revealed three components of terrestrial origin, with certain degree of microbial processing: C1 and C2 (terrestrial humic-like compounds) and C3 (protein-like and pigment derived compounds). Seasonal changes in MOD quality represent different breakdown stages of the allochthonous DOM. Our survey allowed us to record and discuss the effects of the Puyehue–Cordón Caulle eruption, showing that due to the high slopes, high current and discharge of the streams the volcanic material was rapidly exported to the Moreno Lake complex. Overall, this survey underscores the magnitude and timing of the allochthonous input revealing the terrestrial subsidy to food webs in Patagonian freshwaters, which are among the most oligotrophic systems of the world.